2021
DOI: 10.3389/fgene.2021.597566
|View full text |Cite
|
Sign up to set email alerts
|

The Distinct Function of p21Waf1/Cip1 With p16Ink4a in Modulating Aging Phenotypes of Werner Syndrome by Affecting Tissue Homeostasis

Abstract: Human Werner syndrome (WS) is an autosomal recessive progeria disease. A mouse model of WS manifests the disease through telomere dysfunction-induced aging phenotypes, which might result from cell cycle control and cellular senescence. Both p21Waf1/Cip1 (p21, encoded by the Cdkn1a gene) and p16Ink4a (p16, encoded by the Ink4a gene) are cell cycle inhibitors and are involved in regulating two key pathways of cellular senescence. To test the effect of p21 and p16 deficiencies in WS, we crossed WS mice (DKO) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For instance, Zhang Y et al discovered that p16 inhibits cell proliferation and promotes cellular senescence. The absence of p16 significantly rescued the senescent phenotype of WS mice, as evidenced by cellular senescence, apoptosis, increased telomere length, and cell proliferation (Zhang et al, 2021a).…”
Section: Treatmentmentioning
confidence: 95%
“…For instance, Zhang Y et al discovered that p16 inhibits cell proliferation and promotes cellular senescence. The absence of p16 significantly rescued the senescent phenotype of WS mice, as evidenced by cellular senescence, apoptosis, increased telomere length, and cell proliferation (Zhang et al, 2021a).…”
Section: Treatmentmentioning
confidence: 95%
“…Moreover, MSCs differentiated from WS iPSCs have a premature senescence phenotype, including epigenetic and chromosomal structure alteration and premature loss of proliferative potential [ 120 ]. Zhang et al found that p21Waf1/Cip1 and p16Ink4a have distinct functions in modulating aging phenotypes of WS [ 121 ]. Particularly, p21 loss in WS activated severe DDR.…”
Section: Cellular Senescence and Bone-sasp In Natural Aging And Prema...mentioning
confidence: 99%
“…Surprisingly, p16INK4A-and p21-expressing cell populations seem to be different [212], which is contrasting with the lack of senescence in p16INK4A/p21 double knockout animals [251]. Also in the p21-ATTAC model, the clearance of p21-but not p16INK4A-positive senescent cells prevented radiation-induced osteoporosis and bone marrow adiposity [226], supporting the view that p16INK4A-and p21-dependent senescence comprise different and independent pathways [3,5,22,273]. A high number of p21-but not p16INK4A-expressing cells was detected in visceral adipose tissue of obese mice, mostly preadipocytes, endothelial cells, and macrophages [218].…”
Section: P21mentioning
confidence: 99%